The Feasibility of Web-Based Virtual Student Worksheets (LKS) On Disaster Mitigation Materials to Improve Critical Thinking Skills and Learning Outcomes - Linda Halimatus Sa'diah; Wachju Subchan; Imam Mudakir (Eduvest - Journal of Universal Studies, 2022)
The Covid-19 pandemic that hit Indonesia caused panic in the education sector so that the Education office took representative actions to prevent the spread of Covid-19 by carrying out learning activities from home. Learning from home activities need to be supported by the existence of teaching materials that can be used by students, so researchers provide solutions by making the right teaching materials to use. This study aims to obtain web-based virtual worksheets on valid disaster mitigation materials to improve critical thinking skills and learning outcomes. The research includes research and development (RnD) using Thiagarajan's 4D research model consisting of define, design, development and disseminate stages. The research data were obtained from the results of validation carried out by three validators consisting of two expert validators and one user validator. The first expert validator scored 85.48%, the second expert validator scored 97.58% and the user validator scored 95.16%. The average result of the final validation is 92.74% and the criteria are very valid (> 85.01%) so that web-based virtual worksheets are feasible to use or apply.